1996
DOI: 10.1210/endo.137.12.8940334
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of endothelin-1 expression in the bovine corpus luteum: elevation by prostaglandin F 2 alpha.

Abstract: Prostaglandin F2alpha (PGF2alpha) has been recognized as the physiological luteolysin in ruminants and other species for more than three decades; however, the mechanisms involved in its action are poorly understood. We previously have shown that endothelin-1 (ET-1) mediates, at least in part, the action of PGF2alpha, and the current study examines the effect of PGF2alpha on the expression of ET-1 in bovine corpus luteum (CL). Endothelins (ETs) were extracted from CL, collected at various times of the estrous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
51
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 43 publications
2
51
1
1
Order By: Relevance
“…Additionally, as demonstrated in this study, luteal endothelial cells are the predominant site of ppET-1 and NOS mRNA expression, therefore levels found in endothelial cells are indicative of tissue levels. Indeed, our findings in endothelial cells are corroborated by data available on iNOS and ET-1 in corpora lutea of mid cycle (Girsh et al 1996, Milvae 2000, Skarzynski et al 2003. Of particular interest are the inverse relationship between ppET-1 and iNOS observed here.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, as demonstrated in this study, luteal endothelial cells are the predominant site of ppET-1 and NOS mRNA expression, therefore levels found in endothelial cells are indicative of tissue levels. Indeed, our findings in endothelial cells are corroborated by data available on iNOS and ET-1 in corpora lutea of mid cycle (Girsh et al 1996, Milvae 2000, Skarzynski et al 2003. Of particular interest are the inverse relationship between ppET-1 and iNOS observed here.…”
Section: Discussionsupporting
confidence: 90%
“…The compound(s) emanating from the corpus luteum milieu which is responsible for the elevated iNOS expression in freshly isolated endothelial cells is at present unknown. Yet, the fact that iNOS is already elevated in luteal tissue at the mid-late luteal phase (Skarzynski et al 2003) and in endothelial cells of mid cycle (this study) when ET-1 expression is still low (Girsh et al 1996, Milvae 2000 and this study) may suggest that NO regulates steady state luteal function. ET-1, in contrast, is not elevated until luteolysis commences (Girsh et al 1996, Hinckley & Milvae 2001) and therefore would be expected to act mainly during luteolysis.…”
Section: Discussionmentioning
confidence: 59%
“…Namely, pre-exposure of the microenvironment within the bovine mid-CL with PGF2α potentiated the P inhibiting activity of endothelin-1 (ET-1) in the in vitro MDS model, which involves the activation of intracellular Ca 2+ . Consequently, we and others have proposed that a vasoactive peptide such as ET-1 mediates luteolytic actions of PGF2α in the bovine CL [17][18][19]. Recently, we have found that angio- tensin II is a possible additive luteolytic mediator in the bovine CL [20].…”
Section: Discussionmentioning
confidence: 91%
“…These findings strongly suggest that the invasion of immune cells into the regressing CL is the major reason for the increase of TNF-α concentration in the CL at this period. Recently, we and others have shown that the production and release of endothelin-1, a vasoconstrictive peptide originated from endothelial cells, increased in the CL and ovarian venous plasma ipsilateral to the CL from 2 h after PGF2α injection in the cow, and proposed that endothelin-1 interacts with PGF2α as a local luteolytic factor [21][22][23][24]. It is likely that such vasoconstrictive peptides are responsible for an acute response to luteolytic PGF2α in both 1) direct inhibition of P release and 2) a vasoconstriction of arterioles, and thereby they can start an acute depletion of P release followed by a degeneration of CL tissue in which TNF-α plays a major role.…”
Section: Discussionmentioning
confidence: 98%